The Influence of Learning Style on Science Process Skills and Student Learning Outcome of Digestive System Material - Githa Indriana; Melva Silitonga; Fauziyah Harahap (Publikasi Indonesia, 2021)
This study aimed to analyze the learning style on science process skill and learning outcome class XI digestive system in State Senior High School of Kisaran, Asahan. This method applied a descriptive study with a quantitative approach. Samples were taken from four schools, each one class totaling 144 students by using purposive sampling. To obtain the data, the description test was used as a questionnaire to determine student learning styles. The high results are visual with a percentage of 38.19. Then the student science process skills instrument with indicators such as observing, classifying, interpreting, predicting, asking questions, hypothesizing, planning experiments, applying concepts, and communicating in biology learning. The results on science process skills of the digestive system material were categorized as good with a score of 82.06 and the highest indicator for observing obtained a mean score of 86.63.with a very good category and the lowest indicator for applying the concept obtained a score of 79.16 a good category. The learning result test obtained a score of 89,04with a very good category. The high score of C6 was obtained at 91.43. and lowest C5 obtained 72.22.